Randomized comparison between dexmedetomidine and midazolam for prevention of emergence agitation after nasal surgeries - Kurhekar, Pranjali (Saudi J Anaesth, 2018)
BACKGROUND: Emergence agitation (EA) in nasal surgeries is seen in around 22% of patients, which can go to dangerous levels. Dexmedetomidine is effective in prevention of EA in such patients. Midazolam given as premedication fails to prevent EA due to its short half-life. In this study, we compared efficacy of dexmedetomidine and midazolam by intravenous infusion for prevention of EA in adult nasal surgeries. MATERIALS AND METHODS: Seventy patients belonging to American society of anesthesiologist Status I and II, between 18 and 60 years of age posted for elective nasal surgeries were randomly divided into two groups. Group D received intravenous dexmedetomidine 0.5 mcg/kg over 15 min followed by 0.1 mcg/kg/h. Group M received intravenous midazolam 0.02 mg/kg over 15 min followed by 0.02 mg/kg/h. EA scores, emergence times, and hemodynamic parameters were monitored and compared between the groups. Statistical analysis was done by independent t-test, Mann–Whitney U-test, and Chi-square test as applicable. RESULTS: Incidence of EA was comparable between the groups (P = 0.23). Two patients in midazolam group developed dangerous agitation while none in dexmedetomidine group. Patients in midazolam group (12.4%) were agitated even in postoperative period, which was not seen with dexmedetomidine group. Hypotension and bradycardia were seen more in dexmedetomidine group. CONCLUSION: Efficacy of midazolam when given as an intravenous infusion is comparable to dexmedetomidine in prevention of EA in nasal surgeries.